A flexible wide‐field FLIM endoscope utilising blue excitation light for label‐free contrast of tissue. Issue 1 (27th February 2014) - Sparks, Hugh; Warren, Sean; Guedes, Joana; Yoshida, Nagisa; Charn, Tze Choong; Guerra, Nadia; Tatla, Taranjit; Dunsby, Christopher; French, Paul
<x xml:space="preserve">Abstract</x> Fluorescence lifetime imaging (FLIM) has previously been shown to provide contrast between normal and diseased tissue. The study presents progress towards clinical and preclinical FLIM endoscopy of tissue autofluorescence, demonstrating a flexible wide‐field endoscope that utilised a low average power blue picosecond laser diode excitation source and was able to acquire mm‐scale spatial maps of autofluorescence lifetimes from fresh ex vivo diseased human larynx biopsies in 8 seconds using an average excitation power of 0.5 mW at the specimen. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>